2015
DOI: 10.1021/acs.chemrestox.5b00241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pregnancy on the Disposition of 2,2′,3,5′,6-Pentachlorobiphenyl (PCB 95) Atropisomers and Their Hydroxylated Metabolites in Female Mice

Abstract: Chiral PCBs, such as PCB 95, are developmental neurotoxicants that undergo atropisomeric enrichment in non-pregnant, adult mice. Because pregnancy is associated with changes in hepatic cytochrome P450 enzyme activity as well as lipid disposition and metabolism, this study investigates the effect of pregnancy on the maternal disposition of chiral PCBs. Female C57Bl/6 mice (8 weeks old) were dosed daily beginning 2 weeks prior to conception and continuing throughout gestation and lactation (56 days total) with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 67 publications
8
45
1
Order By: Relevance
“…Further complicating the interpretation of the impact of metabolism on PCB developmental neurotoxicity, studies in mice have shown that not only can the tissue distribution of parent PCBs and their metabolites differ, but for chiral PCBs, which includes many RyR-active PCBs, the enantiomeric enrichment of parent versus metabolites can differ in a tissue-specific manner [98]. Furthermore, PCB metabolism can be altered by pregnancy [99]. These studies highlight the need for a better understanding of how the biotransformation of PCBs contributes to overall NDD risk.…”
Section: Neurobehavioral Effects Of Developmental Pcb Exposuresmentioning
confidence: 99%
“…Further complicating the interpretation of the impact of metabolism on PCB developmental neurotoxicity, studies in mice have shown that not only can the tissue distribution of parent PCBs and their metabolites differ, but for chiral PCBs, which includes many RyR-active PCBs, the enantiomeric enrichment of parent versus metabolites can differ in a tissue-specific manner [98]. Furthermore, PCB metabolism can be altered by pregnancy [99]. These studies highlight the need for a better understanding of how the biotransformation of PCBs contributes to overall NDD risk.…”
Section: Neurobehavioral Effects Of Developmental Pcb Exposuresmentioning
confidence: 99%
“…This observation is not surprising given the diversity of expression of cytochrome P-450 enzymes across species. In vivo studies also reveal the formation of chiral OH-PCB metabolites in rats (Kania-Korwel et al 2008c) and mice (Kania-Korwel et al 2015, Kania-Korwel et al 2012, Kania-Korwel et al 2017, Wu et al 2015) exposed orally or intraperitoneally to a racemic PCB congener. There is also evidence that plants, such as poplar plants, metabolize chiral PCBs to chiral OH-PCB metabolites (Ma et al 2016, Zhai et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…18 Studies in pregnant mice exposed to PCB 95 during gestation and lactation showed no detectable levels of 4′-95 in the blood and liver of the dams. 8 …”
mentioning
confidence: 99%